Implementasi Pembelajaran Berbasis Teknologi Informasi (TI) di Taman Kanak-Kanak Bunga Bangsa Islamic School Bekasi - Nadar, Wahyuni (Journal of Early Childhood Education (JECE), 2020)
This research was conducted to describe the results of the analysis of the implementation of IT-based learning at the Bunga Bangsa Islamic Kindergarten Bekasi. The analysis includes the understanding concept of IT-based learning implemented in Bunga Bangsa Islamic Kindergarten, knowing the obstacles in the implementation of IT-based learning there, and describing the strategies carried out in implementing IT learning there. This research was conducted for 3 months with a qualitative descriptive approach. Data collection is done by interviews, observation, analysis of documents in the form of curriculum documents, lesson plan (RPPH), assessment of children's learning outcomes and documentation of the usege of IT tools in learning there. Data analysis begins by describing the findings of the study and then conducts an objective discussion with a theoretical approach. In this study the learning process was described in the Bunga Bangsa Islamic Kindergarten and the usage of technological tools in various aspects of learning components such as media, learning resources and also as learning support. The learning process is more interesting and not monotonous, thus creating a fun and interactive atmosphere. The constraints found were that there was still lack of teacher references for using IT tools for learning in some activities in specific theme and the lack of teachers' skills in using existing IT tools. Current efforts to overcome these obstacles are by providing various references in the form of videos, books and workshops on the use of IT in learning.